A predictive model for seismic displacement of reinforced slopes. Issue 6 (December 2004) - Paulsen, S. B.; Kramer, S. L.
Abstract : Geosynthetic-reinforced soil structures have increased greatly in popularity over the past 20 years. Their adoption for use as permanent structures in seismically active areas, however, has been hindered by uncertainty regarding appropriate seismic design procedures. The development of such procedures requires analytical models capable of predicting the pertinent seismic response of geosynthetic-reinforced structures as a function of all of the significant variables that can be controlled by the designer. Operating under the assumption that permanent deformation is the best indicator of post-earthquake serviceability, this paper describes the development and validation of a practical model for estimation of the permanent displacement of reinforced slopes subjected to earthquake loading. The ability of the model to reasonably predict yield acceleration and time histories of permanent displacement in model tests is demonstrated, and its potential use as a design tool is discussed. A companion paper illustrates the practical use of the model.